2001
DOI: 10.1590/s0004-282x2001000400008
|View full text |Cite
|
Sign up to set email alerts
|

Contribuição à neuropsicologia do comportamento executivo: Torre de Londres e teste de Wisconsin em indivíduos normais

Abstract: RESUMO -O conceito de desempenho executivo se refere a uma coleção de habilidades cognitivas essenciais para a organização do funcionamento mental e comportamental. Investigamos o desempenho executivo de 61 adultos normais com dois testes padrão, o Teste de Wisconsin (TW) e a Torre de Londres (TL). Nosso propósito consistiu em testar as hipóteses de que (i) o desempenho executivo é constituído de dimensões múltiplas como ocorre, por exemplo, com a memória e a linguagem; (ii) o desempenho executivo de indivíduo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
12

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(19 citation statements)
references
References 26 publications
2
5
0
12
Order By: Relevance
“…As previously mentioned, Souza et al (2001) observed no difference in performance in the categories completed and perseverative errors on the WCST between healthy men and women, but differences were found in the other measures of executive function, showing a better outcome in men. However, had significantly higher educational levels than women in the study and this variable may have influenced these results.…”
Section: Blocksupporting
confidence: 53%
See 1 more Smart Citation
“…As previously mentioned, Souza et al (2001) observed no difference in performance in the categories completed and perseverative errors on the WCST between healthy men and women, but differences were found in the other measures of executive function, showing a better outcome in men. However, had significantly higher educational levels than women in the study and this variable may have influenced these results.…”
Section: Blocksupporting
confidence: 53%
“…Women showed a higher degree of depression (Souza, Ignácio Cunha, Oliveira, & Moll, 2001). Additional evidence indicates that women with high depressive symptoms have fewer strategies for coping with emotions compared with men with high depressive symptoms (Thayer, Rossy, Ruiz-Padial, & Johnsen, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…15 Souza et al também observaram associação direta entre anos de estudo e desempenho em teste relacionado à tomada de decisão e à velocidade de processamento; de modo que, quanto menor é a escolaridade, menor a velocidade de processamento e maior a dificuldade em realizar duas ou mais ações paralelamente. 16 No envelhecimento normal, observa-se desempenho prejudicado em funções como atenção, memória de trabalho e velocidade de processamento, 17 funções avaliadas por intermédio do teste de TEVA. 11 A associação observada entre o desempenho no teste de MLP e a idade pode ser justificada pela perda na capacidade de aprendizagem de novas informações, achado inerente ao envelhecimento normal.…”
Section: Discussionunclassified
“…It is suggested that the tests evaluating the executive functions which are dynamic and functional should be well designed and effective at the psychological processes like the usage of the planning strategies and problem solving [34]. Tower tests are thought to include the ability to attempt focused target behaviour, develop strategic sequential planning and application [35]. In the literature tower tests were not used frequently to evaluate the executive functions in alcohol-dependent patients.…”
Section: Discussionmentioning
confidence: 99%